Ideology and Political Orientation of Intellectuals from Koto Gadang 1930-1950: A Prosopography - Nazra Cahyani Endah Regita; Herwandi Herwandi; Nopriyasman Nopriyasman (Diponegoro University, 2022)
Koto Gadang is a traditional village in Minangkabau, which has produced many Indonesian political figures in the period before and during the early days of Indonesian independence. Koto Gadang scholar is an intellectual figure in Indonesian politics in various schools of thought. This study analyses the thoughts of the intellectuals from Koto Gadang; Yahya Datuk Kayo, Agus Salim, Rohana Kudus, Chalid Salim, and Sutan Syahrir; in Indonesian politics 1930-1950. The study shows that the variety of researchers' viewpoints is impacted by family, social, and instructive natural elements, inside and outside Koto Gadang. Yahya Datuk Kayo in the Koto Gadang environment built his region from various aspects, one of which was marked by the construction of Studiefonds [intellectualship foundations]. Rohana Kudus advances the ladies of Koto Gadang through the woman' abilities school, called Keradjinan Amai Setia. Agus Salim's considerations on Islam and his patriotism about the goals of an autonomous Indonesia. Chalid Salim's writings criticizing the colonial government led to him being arrested and imprisoned, in his actions to defend the workers. Sutan Syahrir grew up outside Koto Gadang, his nationalism was under the influence of socialism through the popular revolution he carried out.